Social Interaction between Bugis and Sasak Communities on Maringkik Island - Salsabilla Retno Sedah Mirah Murcahyaningrum; Edy Suyanto; Tri Rini Widyastuti (Sumber Belajar Sejahtera, 2023)
This research aims to analyze the forms of social interaction between Bugis and Sasak communities, as well as the adaptation of Bugis immigrants to the culture and customs of the Sasak community in Maringkik Island. The study employs a qualitative descriptive method with a case study approach. Data collection methods include observation, in-depth interviews, and documentation. Data analysis involves data reduction, presentation in narrative form, and drawing conclusions. The findings of the research indicate that the social interaction between Bugis and Sasak communities in Maringkik Island is characterized by harmony, mutual support, adaptation, economic cooperation, cultural exchange, interethnic marriages, and effective communication. The adaptation of Bugis immigrants to the culture and customs of the Sasak community is evident in their daily interactions. In conclusion, the social interaction between the Bugis and Sasak communities in Maringkik Island is observed to be harmonious, supportive, adaptive, and characterized by effective communication.